Transformasi Kesadaran Kesehatan Masyarakat dalam Program PPKM Mikro: Analisis Kontekstual di Wilayah Pedesaan: Transforming Public Health Awareness in Micro PPKM Programs: Contextual Analysis in Rural Areas - Shofyan Tsauri; Rifa ‘Ulfah; Eki Safitri (AKSIOLOGI: Journal of Community Development, 2025)
This study aims to examine the effectiveness of the PPKM Mikro (Micro-Scale Public Activity Restrictions Team) in raising public awareness and discipline regarding the implementation of Covid-19 health protocols in Sikapat Village, Sumbang Subdistrict. The research is motivated by the observed decline in public compliance with health protocols after the area was declared a green zone. A qualitative method was employed, using data collection techniques such as direct observation and in-depth interviews with the Village Head, Deputy Head of the PPKM Mikro Team, and local community members. The results indicate that the PPKM Mikro Team was relatively effective in promoting health protocol awareness during the early stages of the pandemic, as evidenced by increased public compliance. However, this effectiveness diminished over time, as public alertness declined with the improved status of the area. In conclusion, the success of the PPKM Mikro Team is situational and strongly influenced by social conditions and the community’s perceived risk of Covid-19